2013
DOI: 10.1177/1091581813511995
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity Evaluation of the Dental Resin Monomer Bisphenol A Glycidyl Methacrylate (CAS 1565-94-2) in Mice

Abstract: The reproductive toxicity potential of the dental resin monomer bisphenol A glycidyl methacrylate (BisGMA; CASRN 1565-94-2) was investigated in male and female Crl: CD1(ICR) mice, 4 dosage groups, and 25 mice/sex/group. Formulations of BisGMA (0, 0.008, 0.08, or 0.8 mg/kg/d) in 0.8% ethanol in deionized water were intubated once daily beginning 28 days before cohabitation and continuing through mating (males) or through gestation day 17. The following parameters were evaluated: viability, clinical signs, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Generally, the highest BIS-GMA release was seen in the first 24 hours, and the amount of residual monomer decreased in the following days. (Moilanen et al (2013), Polydorou et al (2009), Ferracane (1994) In our study, the highest Bis-GMA release was observed in 3 different composite materials within the first 24 hours. Composite contains 1-10% Bis-GMA, flowable composite contains 1-10% Bis-GMA, bulk fill composite contains 2.5-10% Bis-GMA.…”
Section: Research Findingssupporting
confidence: 49%
“…Generally, the highest BIS-GMA release was seen in the first 24 hours, and the amount of residual monomer decreased in the following days. (Moilanen et al (2013), Polydorou et al (2009), Ferracane (1994) In our study, the highest Bis-GMA release was observed in 3 different composite materials within the first 24 hours. Composite contains 1-10% Bis-GMA, flowable composite contains 1-10% Bis-GMA, bulk fill composite contains 2.5-10% Bis-GMA.…”
Section: Research Findingssupporting
confidence: 49%
“…The availability of data on the recommended intake limits of monomers is limited. Moilanen et al [38,39] conducted studies on acute toxicity after ingestion of BisGMA, TEGDMA, and UDMA in rats and reported LD50 values of 2, 10.837, and 5 mg/kg, respectively. The studies also identified no observed adverse effect level (NOAEL) for reproductive toxicity in mice for BisGMA and TEGDMA, which was 0.8 and 1 mg/kg bw/day, respectively, based on daily exposure for more than a month.…”
Section: Discussionmentioning
confidence: 99%
“…Leachable components from conventional materials include the actual monomers and some of their degradation products, such as triethylene glycol and bishydroxypropoxy-phenyl propane [69,70]. These products have been demonstrated to regulate bacterial adhesion and colonization [71,72], as well as to pose potential toxicity concerns, especially when used in dental adhesives [72][73][74][75]. Several direct restorative materials are in fact conducive of biofilm colonization, and therefore, antimicrobial composites have also been proposed [76,77].…”
Section: Incomplete DC Depth Of Cure and Materials Degradationmentioning
confidence: 99%